A 12 dB 0.7 V 𝟖𝟓𝟎𝝁W CMOS LNA for 866 MHz UHF RFID Reader - Jie Li; S. M. Rezaul Hasan (Active and Passive Electronic Components)
The design of a narrow-band cascode CMOS inductive source-degenerated low noise amplifier (LNA) for 866 MHz UHF RFID reader is presented. Compared to other previously reported narrow-band LNA designs, in this paper the finite 𝑔ds  (=1/𝑟0) effect has been considered to improve the nanometric design, achieving simultaneous impedance and minimum 𝐹min noise matching at a very low power drain of 850 𝜇W from a 0.7 V supply voltage. The LNA was fabricated using the IBM 130 nm CMOS process delivering a forward power gain (𝑆21) of ≈12dB, a reverse isolation (𝑆12) of ≈−34dB, an output power reflection (𝑆22 @866 MHz) of ≈−25dB, and an input power reflection (𝑆11 @866 MHz) of ≈−12dB. It had a minimum pass-band 𝑁𝐹 of around 2.2 dB and a third-order input referred intercept point (IIP3) of ≈−11.5dBm.